Application of Nanofluids in Rapid Methane Hydrate Formation: A Review - Qin, Yue; Shang, Liyan; Zhou, Li; Zhu, Jian; Yuan, Song; Zang, Chunyang; Ao, Di; Li, Zeting (Energy & fuels, 2022)
The use of hydrate-based technologies for gas storage and transportation, carbon capture and sequestration, desalination, and cold energy utilization is gaining popularity. Unfortunately, the slow formation kinetics of hydrates constrains the development of these technologies. Nanofluids have received widespread attention as they can effectively improve the formation kinetics of hydrates. Accordingly, this review examines the history of nanofluid use in rapid hydrate formation as well as the mechanisms of action of various nanofluids. Furthermore, the performance of various nanofluids is fairly assessed, and their performance is compared to that of other systems. Finally, current nanofluid challenges and constraints are discussed, as well as future development recommendations.